2019
DOI: 10.15252/embr.201949354
|View full text |Cite
|
Sign up to set email alerts
|

Response to: X‐linked miR‐506 family miRNAs promote FMRP expression in mouse spermatogonia

Abstract: EMBO Reports (2020) 21: e49354Reply to: Z Wang et al T he topic of this rebuttal is a set of miRNAs expressed from a large gene cluster located in the Fragile-X region of the X chromosome that we call the "Fragile-X miRNA (Fx-mir) cluster". This miRNA cluster has several other names. Wang et al calls them the "miR-506 family", as some members of this cluster are related to this particular miRNA. Other names for this cluster from recent papers are "spermiR" [1] and "XmiR" [2].In our Ramaiah et al [3] paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Second, the authors demonstrated that the miR-506 family miRNAs showed elevated levels in germ cell-deficient testes of mice (jsd/jsd mice) and humans (Sertoli cell-only (SCO) patients) compared with normal controls. However, the testes of jsd/jsd mice are known to contain some spermatogonia, albeit in a small number [13], and SCO human testes may also contain some germ cells, as acknowledged by the authors as well [5]. Therefore, qPCR-based detection of the miR-506 family miRNAs in these so-called germ cell-deficient testes cannot exclude their expression in spermatogonia.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the authors demonstrated that the miR-506 family miRNAs showed elevated levels in germ cell-deficient testes of mice (jsd/jsd mice) and humans (Sertoli cell-only (SCO) patients) compared with normal controls. However, the testes of jsd/jsd mice are known to contain some spermatogonia, albeit in a small number [13], and SCO human testes may also contain some germ cells, as acknowledged by the authors as well [5]. Therefore, qPCR-based detection of the miR-506 family miRNAs in these so-called germ cell-deficient testes cannot exclude their expression in spermatogonia.…”
mentioning
confidence: 99%
“…The close proximity between the miR-506 family and Fmr1 has prompted a hypothesis that Fmr1 might be a target of the miR-506 family. A recent paper by Ramaiah et al reports that the miR-506 family miRNAs, which they termed Fx-mir miRNAs, function to repress Fmr1 (encoding FMRP) expression in Sertoli cells based on expression profiling analyses and luciferase-based reporter assays in vitro [5]. Our laboratory first reported the exclusive or preferential expression of 77 Xlinked miRNAs in the murine testes [3], and we happen to have generated knockout (KO) mice lacking the five miRNA clusters encoding 18 out of 21 miR-506 family miRNAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation